Psychosocial Processes Linked to Memory and Forgiveness in Mobilized Victims in Colombia - Revelo, Diana Rico; Garrido, Hellen Cristancho [UNESP]; de la Cruz Barrios, Andrea; Alzate, Mónica (Universidad de los Andes, 2023)
In a context marked by various transitional justice processes and still affected by dynamics of violence, in this article, we analyze psychosocial dimensions related to forgiveness and memory in experiences of members of social organizations who are victims of the Colombian armed conflict. The aim is to explore cognitive, emotional, and attitudinal processes that hinder or enable forgiveness. A mixed-methodology was used, with two studies conducted in the departments of Atlántico and Caldas. In the first study, a phenomenological design was applied to uncover ideas and emotions regarding memory and forgiveness among leaders of victim collectives. In the second study, a non-experimental design was implemented to analyze the interaction between three factors explaining the disposition to forgive (DP): enduring resentment (RD), sensitivity to circumstances (SC), and unconditional forgiveness (PI). The qualitative study revealed meanings surrounding memory that constrain forgiveness (RD, exclusive victim beliefs, and perceived obstacles to the effectiveness of transitional justice measures), as well as memory resignifications that promote forgiveness (understanding of the conflict, inclusive victim beliefs, memory linked to transitional justice, and PI). The quantitative study indicated that SC explains PI, while RD poses an obstacle. The research progresses towards a deeper comprehension of the connection between memory and forgiveness in transitional settings, unveiling challenges in effectively managing memory with forgiveness in mind. It highlights the significance of addressing RD and fostering SC to facilitate forgiveness, not only at the national level but also at the local and regional scales.
Procesos psicosociales vinculados a la memoria y al perdón en víctimas movilizadas en Colombia
Processos psicossociais ligados à memória e ao perdão em vítimas mobilizadas na Colômbia
Keywords: forgiveness; memory; resentment; sensitivity to circumstances; victims